Sixty Years of UGM Forestry Faculty’s Work in Preserving Indonesia’s Forests and Environment - Sigit Sunarta; Kaharuddin Kaharuddin; Dwiko Budi Permadi; Widiyatno Widiyatno; Ragil Widyorini; Greitta Kusuma Dewi; Ari Susanti; Ni Putu Diana Mahayani (Jurnal Ilmu Kehutanan, 2024)
Given a mandate to preserve the Indonesia tropical forest through its education, research, and community service activities, the Faculty of Forestry Universitas Gadjah Mada (FoF UGM) has reached broad stakeholders to support sustainable forest management and climate mitigation (SDG 13 and 17). FoF UGM supports basic and applied research contributing to forestry industrialization (SDG 9), such as improved planting materials for Tectona grandis and Eucalyptus sp. In collaboration with the community (SDG 1 and 2), FoF UGM also diversifies kajuput essential oil produced in Wanagama and UGM teaching forests. Technology innovations such as glue and cross-laminated timber, biodiesel, information systems, and drone technologies for land rehabilitation and carbon accounting represent the institution's commitment to improving Indonesia's forest, forestry, community, and national economy (SDG 13 and 15).